Some Inconvenient Truths about Climate Change Policy: The Distributional Impacts of Transportation Policies - Holland, Stephen P.; Hughes, Jonathan E.; Knittel, Christopher R.; Parker, Nathan C. (The Review of Economics and Statistics, 2015)
Climate policy has favored costly measures that implicitly or explicitly subsidize lowcarbon fuels.We simulate four transportation sector policies: cap and trade (CAT), ethanol subsidies, a renewable fuel standard (RFS), and a lowcarbon fuel standard. Our simulations confirm that alternatives to CAT are 2.5 to 4 times more costly but are amenable to adoption due to right-skewed distributions of gains. We analyze voting on the Waxman-Markey (WM) CAT bill. Conditional on a district’s CAT gains, a district’s RFS gains are negatively correlated with the likelihood of voting for WM. Our analysis supports campaign contributions as a partial mechanism.